Assessment of RC walls with cut-out openings strengthened by FRP composites using a rigid-plastic approach. (1st November 2017) - Popescu, Cosmin; Schmidt, Jacob W.; Goltermann, Per; Sas, Gabriel
Highlights: RC walls under transverse loading exhibit a ductile failure mechanism. RC walls under axial loading exhibit a brittle failure mechanism. Limit analysis approach is used to predict the ultimate capacity. The CFRP contribution is accounted through an updated concrete model. Abstract: Building refurbishment works frequently require the cutting of new openings in concrete walls. Cutting new openings weakens the overall response of such elements, so they usually require strengthening. However, current design codes offer little guidance on strengthening walls with openings, and less still on the use of non-metallic reinforcements such as FRP (Fibre Reinforced Polymers) to ensure sufficient load bearing capacity. This paper proposes a new procedure based on limit analysis theory for evaluating the ultimate load of walls with cut-out openings that have been strengthened with carbon-FRP (CFRP). First, the approach is verified against transverse (out-of-plane) and axial (in-plane) loading for unstrengthened specimens. These loading types result in different failure mechanisms: transverse loading leads to failure due to yielding/rupture of the steel reinforcement while axial loading leads to failure by concrete crushing. Second, the proposed method is further developed for CFRP-strengthened specimens under axial loading. It accounts for the contribution of CFRP indirectly, by updating the concrete model with an enhanced compressive strength as a result of confining the piers. Predictions made using the new method agree closely with experimental results.